1988
DOI: 10.1021/ja00228a033
|View full text |Cite
|
Sign up to set email alerts
|

Thermotropic properties of synthetic chain-substituted phosphatidylcholines: effect of substituent size, polarity, number, and location on molecular packing in bilayers

Abstract: Differential scanning calorimetry has been applied to aqueous suspensions comprised of synthetic phospholipids on whose chains reside substituents of diverse size (methyl, n-butyl, phenyl), polarity (alkyl, keto), number (one or both chains), and location (carbons 4, 6, 8, 10, 12, or 16 of 18-carbon chains). Attention focused primarily on the "main" phase transition in the lipid bilayers resulting from disordering ("melting") of the hydrocarbon tails. The thermotropic behavior revealed, among the more interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 0 publications
3
29
0
Order By: Relevance
“…Thermal analysis: Previous studies have shown that a methyl branchings into alkyl chains lowers the phase transition temperature (T m ), [29] and that Halobacterium lipids bearing several methyl-branched terpenyl chains exhibit no detectable gel-to-liquid crystalline phase transition over a wide range. [30] In our case the liposomes of archñal lipids (macrocyclic lipid A, diphytanylphosphatidylcholine B, diphytylphosphatidylcholine C and digeranylgeranylphosphatidylcholine D) also did not show any phase transition between À 40 and 60 8C.…”
Section: Resultsmentioning
confidence: 99%
“…Thermal analysis: Previous studies have shown that a methyl branchings into alkyl chains lowers the phase transition temperature (T m ), [29] and that Halobacterium lipids bearing several methyl-branched terpenyl chains exhibit no detectable gel-to-liquid crystalline phase transition over a wide range. [30] In our case the liposomes of archñal lipids (macrocyclic lipid A, diphytanylphosphatidylcholine B, diphytylphosphatidylcholine C and digeranylgeranylphosphatidylcholine D) also did not show any phase transition between À 40 and 60 8C.…”
Section: Resultsmentioning
confidence: 99%
“…DSC thermograms of the lipid bilayers, composed of DMPC lipids and small amounts of incorporated fatty acids, revealed two major thermic events (Mabrey and Sturtevant, 1976;Lewis et al, 1987a,b;Menger et al, 1988). Upon an increase in temperature, an endothermic pre-transition state was found between 9 and 19 • C (data not shown), followed by the main phase transition state (T m 22-25 • C, Table 1).…”
Section: Membrane Phase Behaviourmentioning
confidence: 94%
“…The impact of both, bound and free fatty acids on the physiological properties of biological membranes was repeatedly studied by calorimetry in the last two decades (Schullery et al, 1981;Blume, 1983;Lewis et al, 1987a,b;Lewis et al, 1988;Menger et al, 1988;Langner and Hui, 2000;Funari et al, 2003;Lindström et al, 2006;Rogerson et al, 2006). For this purpose, phospholipid composed model bilayers were subjected to a temperature-induced phase transition from the relatively ordered state L ␤ gel phase to a more disordered, but biological active liquid-crystalline state, which prevails at 37 • C in humans.…”
Section: Introductionmentioning
confidence: 99%
“…However, the sharpness of the melting peak can be influenced by factors such as purity and crystalline defects. Ramifications near the headgroup are relatively immobilized, whereas carbon atoms near the terminal end are quite mobile [59]. Moreover, the melting temperature is less defined as the concentration of impurities increases (Fig.…”
Section: A Meltingmentioning
confidence: 99%